Fragmented practice : creating and maintaining information-rich websites in SMEs - Burford, Sally (2021)
Background. Whilst designing and implementing optimal Web information structures contributes to organisational goals and success, the size and structure of small and medium enterprises (SMEs) make Web information architecture (IA) a challenging task. At the same time, the attitudes and the capabilities of SMEs for online participation are crucial to a robust economy in nations across the world. Objectives. This research aimed to better understand the context and activity in the development of an information-rich website in SMEs in Australia. The particular issues, obstacles and successes in the practice of IA in SMEs are explored. Methods. Framed by a multi-case study methodology, this research used SMEs as units of analysis. In an inductive approach to analysis, the data were coded using NVivo software to reveal patterns and themes common across the studied SMEs. Results. The context for the development of online information structures is a fragmented Web development process. Web information structures are not always effective and SMEs are challenged to maintain an IA once a new website is launched. Contributions. This study suggests that Web IA and its allied practices are severely under-researched and under-theorised in SMEs. Whilst SMEs exert significant effort in the development of an information-rich website, they are poorly informed or influenced by expertise and theory. Staff with the knowledge and attitude needed to embed effective IA in the development and maintenance of the enterprise website are crucial in ensuring that the organisation’s online strategy is achieved.